Precast prestressed hollow core floors. (FIP recommendations., 1988)
These recommendations, together with a detailed commentary, are the result of nine years' intensive research. They provide the engineer and precaster with a guide to sound design and put at their disposal calculation methods and examples of good practice for the many details of the design of hollow core floors.